School-to-Work Transitions Before, During and After the Global Financial Crisis in Australia - Chesters, Jenny; Baffour, Bernard (My University, 2015)
School-to-work transitions are increasingly contingent upon having appropriate educational credentials therefore leaving school before completing secondary education may result in young people experiencing prolonged periods of precarious employment. Although the Australian economy weathered the recent Global Financial Crisis (GFC) better than many other advanced economies, in August 2009 the combined unemployment and underemployment rate for young people was double the rate for the working age population. During economic recessions, young people tend to delay entry into the labour market preferring remain in school until the economy rebounds and jobs are easier to secure. This paper presents the results of analyses of the Household Income and Labour Dynamics in Australia data tracking the fortunes of three cohorts of young Australians: those who completed school prior to the GFC; those who completed school during the GFC; and those who completed school after the GFC to examine the effect of the crisis on school-to-work transitions.
Australian Journal of Labour Economics
Keywords: Employment -- Entry to employment; Employment -- Unemployment; Employment -- Security of employment; Labour market; Employment; Security of employment; Unemployment; Entry to employment; Employment and unemployment